PENERAPAN SANKSI HUKUM ADAT DI KAWASAN OMBO DESA WABULA KECAMATAN WABULA KABUPATEN BUTON - Leos Davfid; Hardi Done; Samaluddin Samaluddin (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2022)
This study aims to find out two things, first to find out the application of customary law sanctions in the ombo area of ​​Wabula Village, Wabula District, Buton Regency and to find out what are the obstacles in the application of customary sanctions in the ombo area of ​​Wabula Village, Wabula District, Buton Regency. The research was conducted in the Ombo area, Wabula Village, Wabula District, Buton Regency, with the research method using data collection techniques by means of library research and field research. The results show that, the application of customary law sanctions, by traditional leaders and Parabela in the customary law area (Ombo) is still respected and upheld by the local indigenous community, customary law sanctions are still applied to anyone who violates customs in the Ombo area, Wabula Village. Wabula District, Buton Regency, while the obstacles in the application of customary law sanctions in the Ombo Area, Wabula Village, Wabula District, Buton Regency are almost non-existent because the community still upholds the level of sacredness of customs and culture so that what has been determined by traditional institutions is always obeyed by the community, even if there are obstacles. only on the application of customary law sanctions to people from outside the Wabula who then commit violations by entering the ombo area.